Abusive Events at Work among Young Working Adults: Magnitude of the Problem and its Effect on Self-Rated Health - Vaez, Marjan; Ekberg, Kerstin; Laflamme, Lucie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2004)
The study examines the incidence of abusive events at work and compares the self-rated health (SRH) assessments of young workers according to whether they have been victims or not. Subjects and materials were extracted from a data set covering the environmental and health conditions of the population of the Östergötland region in Sweden. The focus was on people in paid employment aged 20–34 years. It appears that threats or acts of violence are more common than are bullying or sexual harassment among young working people, in particular among women. Further, when working conditions are relatively precarious, both men and women are comparably exposed to threat and violence but when conditions are more stable, women are proportionally more exposed than men. Furthermore, the study shows that, although less common than threat and violence are, exposure to bullying is associated with several SRH disorders among both men and women in employment.